Uma sequência didática para o ensino de poliedros explorando o movimento lógico-histórico do conceito - Lima, Wilson Francisco da Rocha (Universidade Federal de São Carlos, 2017)
The purpose of this work is comprehend and bring to the classroom environment a trajectory of the polyhedron as a concept through the history of human knowledge seeking to answer the following question: How would a didactic sequence that addressed the contents related to polyhedra that make up the curriculum of current Mathematics classes in a critical way, contextualizing the knowledge with the historical moment in which it was developed and articulating the contents with current researches of Scientific Mathematics? With Vygotsky's socio interactionist theory and Marx's dialectical materialism as a background, this work explores the presence of History of Mathematics on education in a sociocultural perspective, considering teaching-learning situations that can provide means of dialogue between the school culture and the one which the concept being taught initially appeared. Using as methodology the Didactic Engineering, a didactic sequence divided into three teachinglearning situations about polyhedrons was elaborated according to the curriculum and applied to middle school students. Based on the works of Greek philosophers Plato and Euclid and the Swiss mathematician Leonhard Euler, the sequence explores from main aspects of geometrical figures to the origins of Topology as an introduction to the conception of tridimensional objects on that field of Mathematics
Keywords: História da matemática; Geometria; Poliedros; History of mathematics; Geometry; Polyhedron; CIENCIAS EXATAS E DA TERRA::MATEMATICA::GEOMETRIA E TOPOLOGIA